Multispecies homescapes - Schuurman, Nora (Sage, 2025)
This paper proposes a change in the conceptualisation of home, as part of a wider paradigmatic transformation in the understandings of the boundaries between humans and animals, and nature and culture. A new concept of multispecies homescapes is suggested, building on recent work on human–animal relationships as well as writings on the home in human geography. Multispecies homescapes are approached as imaginary spaces, including experiences of sharing home with other species, the limits and liminalities of homeness, and the loss of a multispecies home. Imagining home as multispecies will widen the scope of research beyond anthropocentric understandings of domestic space.